Perancangan Mesin Bending untuk Menurunkan Reject Mechanical Packing Kapasitor - Siboro, Benedikta Anna Haulian; Afma, Vera Methalina; Pratama, Ardi (Jurnal Sistem dan Manajemen Industri, 2018)
In order to increase productivity required synergizing and balancing all components in the work system. The achievement of labor productivity through activity sustainable done at one manufacturing companies who produce capacitor. In the packing process is done manually using bending tools that cause fatigue 90-95% tired on the right foot and right hand, with the average reject 14% and only meet 66% output target. The purpose of this research is make a bending machine to increase the capacity process of packing, so it expected to decrease reject mechanical and indirectly decrease the work load operator. The design of the bending machine is done by testing the T-test statistic (paired T-test) against the mechanical reject by making the machine system semi-automatic with motor and engine control on the machine table design using the average height of the operator seat with the aim that the standard time can be faster, The human workload based on the man machine system may decrease.  The result of bending machine design shows that the standard time after design is increased from 1.52 seconds to 1.02 seconds so the average output increase from 16578 capacitors to 24705 capacitors. The reject mechanical fell significantly from the average total of 2210  to an average total of 446  and the man workload in this study decreased from 25.29 minutes to 6.23 minutes, so the production target could be met.